FPGA Based Fault Distance Detection and Positioning of Underground Energy Cable by Using GSM/GPRS - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper proposes the usage of Field Programmable Gate Arrays (FPGA) for fault distance detection and positioning of an underground cable by using GSM/GPRS. This task was produced using Very High Speed Integrated Circuit Hardware Description Languages (VHDL) and implemented on Basys-3 FPGA board by using Xilinx Vivado Design Suite 18.1. Deciding the separation of underground power line fault from the base station was done by using FPGA and Global System for Mobile Communication/General Packet Radio Service (GSM/GPRS) module. The main fault types are three phase symmetrical short circuit fault, two phase-to-earth short-circuit fault, phase-to-phase short circuit fault, phase-to-earth short circuit fault and open-circuit fault. In this study, only two types of faults were taken into consideration. The first of them is phaseto-earth short-circuit fault, while the other one is open circuit fault with broken in transmission line and both simulated by using LTspice. © 2019 IEEE.
Keywords: Basys-3 board; FPGA; FSM (Finite State Machine); LTspice; SIM900 GPRS/GSM Module; Smart phone; VHDL